Population dynamics of cyanomyovirus in a tropical Eutrophic reservoir - Yeo, Bee Hui (2015)
Samples from three stations in Kranji Reservoir, Singapore (n = 21) were collected and analyzed for cyanomyovirus abundance and diversity. A total of 73 different g20 (viral capsid assembly protein genes) amino acid sequences were obtained from this study. A phylogenetic analysis revealed that the 73 segments were distributed in six major clusters (α to ζ), with four unique subclusters, which were identified as KRM-I, KRM-II, KRM-III, and KRM-IV. The cyanophage community in Kranji Reservoir exhibited a large degree of diversity; the clones obtained in this study showed similarities to those from many different environments, including oceans, lakes, bays, and paddy floodwater, as well as clones from paddy field soils. However, the sequences in this study were generally found to be more closely related to the g20 sequences of freshwaters and brackish waters than those from marine environments. The rarefaction curves and Chao 1 indices from this study showed that the diversity of the cyanomyovirus community was greater during the Inter-monsoon periods than the Southwest and Northeast Monsoons. A few seasonal changes in the taxa were observed: (i) Cluster ζ was absent during the Southwest Monsoon, and (ii) most of the samples fell into Group 3 in the PCA score plot during the Northeast Monsoon, and the fraction of Cluster ɛ increased significantly.